2003
DOI: 10.1016/s0014-5793(03)01400-5
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid phase transitions in homogeneous nanometer scale bilayer discs

Abstract: Nanoscale protein supported phospholipid bilayer discs, or Nanodiscs, were produced for the purpose of studying the phase transition behavior of the incorporated lipids. Nanodiscs and vesicles were prepared with two phospholipids, dipalmitoyl phosphatidylcholine and dimyristoyl phosphatidylcholine, and the phase transition of each was analyzed using laurdan £uorescence and di¡erential scanning calorimetry. Laurdan is a £uorescent probe sensitive to the increase of hydration in the lipid bilayer that accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
141
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 26 publications
23
141
0
Order By: Relevance
“…Disk-to-vesicle conversion was also evident from the DSC data recorded in repetitive scans of the same sample (Fig. 3B, solid and dashed lines): the fi rst heating scan showed a relatively broad gelto-liquid crystal phase transition centered at 26°C, which is characteristic of discoidal rHDL, whereas the second scan showed a sharper transition (refl ecting larger cooperative unit) that was shifted to T c = 24°C, which is characteristic of DMPC vesicles ( 47 ). Furthermore, compared with the fi rst heating scan, consecutive heating scans monitored by DSC and CD resulted in lower apparent melting temperature T m (Fig.…”
Section: Effects Of Cholesterol On the Structure And Stability Of Apomentioning
confidence: 71%
“…Disk-to-vesicle conversion was also evident from the DSC data recorded in repetitive scans of the same sample (Fig. 3B, solid and dashed lines): the fi rst heating scan showed a relatively broad gelto-liquid crystal phase transition centered at 26°C, which is characteristic of discoidal rHDL, whereas the second scan showed a sharper transition (refl ecting larger cooperative unit) that was shifted to T c = 24°C, which is characteristic of DMPC vesicles ( 47 ). Furthermore, compared with the fi rst heating scan, consecutive heating scans monitored by DSC and CD resulted in lower apparent melting temperature T m (Fig.…”
Section: Effects Of Cholesterol On the Structure And Stability Of Apomentioning
confidence: 71%
“…The lipid composition is also tuneable because it is possible to add cholesterol and/or charged lipids 17. Lipid physical properties in nanodiscs have been studied and compared with existing membrane models by different biophysical techniques, such as small‐angle X‐ray scattering (SAXS),9, 10, 35, 40 small‐angle neutron scattering (SANS),35, 41 NMR spectroscopy31, 34 or fluorescence spectroscopy 35, 39. Although a general consensus concerning the driving force of nanodisc assembly and the resulting MSP architecture exists nowadays,5, 11 little is known about the internal dynamics of lipids and membrane proteins embedded in nanodiscs, as well as how the lipid–lipid and lipid–protein dynamic interplay influence the membrane protein activity.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that reconstituted high-density lipoproteins (rHDLs), which are also known as nanodiscs (29), can accommodate membrane proteins within a 10-nm-diameter diskshaped lipid bilayer (30). The rHDLs reportedly provide a lipid environment with more native-like properties, compared with liposomes, in terms of the lateral pressure and curvature profiles because detergent micelles have strong curvature and different lateral pressure profiles from lipid membranes (31). Our NMR analyses of a G protein-coupled receptor (GPCR) and an ion channel in rHDL lipid bilayers revealed that the population and the exchange rates of the conformational equilibrium determine their signal transduction and ion transport activities (32)(33)(34) and that the population of the active conformation of the GPCR in rHDLs correlated better with the signaling levels than that in detergent micelles (32).…”
mentioning
confidence: 99%